Influence of Corrosion on Thermo-Mechanical Contact Fatigue in Rolling Conditions with Low Amplitude Sliding - S. Mistreanu; F. Tudose-Sandu-Ville; C. Munteanu; R. Cimpoesu; M. Lutcanu; I. Știrbu; V. Manole; C. Stamate; O. Rusu; N. Cimpoeșu (Archives of Metallurgy and Materials)
The paper presents some aspects concerning mechanical contact fatigue and corrosion wear and the links of these two kinds of wear in the common deterioration of the contact layer. The surface state, for both presented areas, is analyzed using scanning electron microscopy (SEM) and energy dispersive spectroscopy (EDS) in order to confirm the double action of corrosion and wear during the experimental test. 2 and 3D insights were taken from the worn area, corrosion compounds were identified and analyzed. Linear and cyclic potentiometry were performed on the base materials after the OCP was established in salt solution. When the level of the thermal and the mechanical stress are located at the same depth under the contact surface the resulting stress is greater and has the opportunity to develop the first crack to the surface. The metallic material surface presents a double type of corrosion: one based on oxidation and the other one based on oxidation plus wear (tribo-corrosion), the difference is being given by the material quantity and type involved.